Socialist China, capitalist China [ social tension and political adaptation under economic globalization - Lansdowne, Helen , 1958-; Wu, Guoguang (China policy series, 2009)
China and the new international order / edited by Wang Gungwu and Zheng Yongnian -- China's opening society : the non-state sector and governance / edited by Zheng Yongnian and Joseph Fewsmith -- Zhao Ziyang and China's political future / edited by Guoguang Wu and Helen Lansdowne -- Hainan - state, society, and business in a Chinese province / Kjeld Erik Brodsgaard -- Non-governmental organizations in China : the